Find all real solutions to the equation above. If your solution set is ; ; then submit your answer as .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If the system has real solutions then 2 − x − y ≥ 0 ⟹ x + y ≤ 2
Using A.M.-G.M. x + y ≥ 2 x y .So, 2 ≥ x + y ≥ 2 x y ⟹ x y ≤ 1
Now consider the expression x 3 y + y 3 x = x y ( x 2 + y 2 ) = x y [ ( x + y ) 2 − 2 x y ] = x y ( x + y ) 2 − 2 ( x y ) 2
Using the two inequalities x + y ≤ 2 and x y ≤ 1
x y ( x + y ) 2 ≤ 1 × 4 = 4 and 2 ( x y ) 2 ≤ 2
So, x y ( x + y ) 2 − 2 ( x y ) 2 ≤ 2 ⟹ x 3 y + y 3 x ≤ 2 ⟹ x 3 y + y 3 x − 2 ≤ 0
This says ∣ 2 − x − y ∣ ≤ 0 which is only possible if the equality holds (which is equal to zero).
So,the only solution is x = y = 1